Medical Device Materials III : Proceedings from the Materials & Processes for Medical Devices Conference 2005, November 14-16, 2005, Boston, Massachusetts, USA - Venugopalan, Ramakrishna; Wu, Ming Hsiung (ASM International, 2006)
The Materials & Processes for Medical Devices Conference focuses on the materials science and engineering aspects of the medical devices industry. Device manufacturers, materials providers, and clinicians share information and knowledge on materials and their properties. Coverage ranges from cardiovascular devices to orthopedics to dental appliances. --